2019
DOI: 10.1111/mcn.12889
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of age‐appropriate breastfeeding, dietary diversity, and consumption of animal source foods among Indonesian children

Abstract: Global child feeding practices remain suboptimal. In this study, we assess the determinants of age-inappropriate breastfeeding, dietary diversity, and consumption of 3+ types of animal source foods (ASFs) using 11,687 observations from combined data from the Indonesian Demographic Health Survey of 2012 and 2017. We used linear and logistic regression after adjusting for the complex sampling design. Child's age and quality of antenatal care (ANC) were associated with all outcomes. Socioeconomic status and labou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 31 publications
3
31
0
1
Order By: Relevance
“…In LMIC, maternal education is a prevailing determinant of children's dietary diversity (Blackstone & Sanghvi, 2018;Choudhury, Headey, & Masters, 2019;Senarath et al, 2012), whereas agroecological factors show context-specific results (Choudhury et al, 2019). Moreover, a study in neighbouring Indonesia found that determinants of young children's DDS and ASF intake included mother's knowledge-combining education level and media access, as well as socio-economic status (Sebayang et al, 2019). Yet we found the intragroup WI to be non-significant, probably due to included suku falling in the lowest national living standards (ADB, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In LMIC, maternal education is a prevailing determinant of children's dietary diversity (Blackstone & Sanghvi, 2018;Choudhury, Headey, & Masters, 2019;Senarath et al, 2012), whereas agroecological factors show context-specific results (Choudhury et al, 2019). Moreover, a study in neighbouring Indonesia found that determinants of young children's DDS and ASF intake included mother's knowledge-combining education level and media access, as well as socio-economic status (Sebayang et al, 2019). Yet we found the intragroup WI to be non-significant, probably due to included suku falling in the lowest national living standards (ADB, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…According to a study by Jannat et al (2020), single mothers tend to choose to buy fast and cheap side dishes because it saves time and is following their income. The provision of foods that do not contain balanced nutrition contributes to the child's survival (Sebayang et al, 2020). Lack of protein consumption causes growth failure and increases death from a heart attack in adulthood (Martony et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…9,40 Berdasarkan analisis data pada Riskesdas 2013 dan 2018, penyebab lain yang memengaruhi ASI eksklusif adalah k ondisi sosioekonomi dan kualitas asuhan antenatal. 41 Kualitas antenatal ini berkaitan dengan persepsi ibu yang kemudian meningkatkan keberlangsungan ASI eksklusif (OR 1.60; IK95% 1.19-2.17). 28 Selain itu, hambatan ASI eksklusif di Indonesia antara lain adalah pengetahuan ibu, kualitas dan kuantitas ASI eksklusif, kurangnya political will dari pemerintah, serta promosi susu formula yang tidak dibatasi.…”
Section: Pembahasanunclassified